Accommodation Licensing Compliance in Halal Tourism Development: Evidence from Dieng Plateau, Indonesia - Rahmaliya, Bani; Huda, Muhammad Chairul; Samson, Nur Aida Tahirulla (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
The rapid growth of accommodation businesses in the Dieng tourism area has not been accompanied by adequate compliance with business licensing regulations, despite the region’s promotion as a halal tourism destination. This condition raises significant legal, governance, and consumer protection issues, particularly in relation to the implementation of halal tourism principles. This study aims to examine accommodation licensing procedures and their practical implementation from a halal tourism perspective in Patakbanteng Village and Dieng Village, Kejajar District, Wonosobo Regency. The research adopts a qualitative field study design with an empirical juridical approach. Data were collected through in-depth interviews with accommodation business operators and relevant government officials, field observations, and documentation, and were analyzed using the interactive model of Miles and Huberman. The findings reveal that compliance with accommodation licensing requirements remains low, especially among small-scale businesses such as homestays and cabins. The main obstacles are not merely regulatory complexity but also limited legal literacy, administrative constraints, and the perception among business owners that licensing provides minimal direct benefits to business sustainability. From a halal tourism perspective, weak business legality undermines effective supervision of halal standards, safety, and comfort for Muslim tourists. This study concludes that business licensing constitutes a strategic legal instrument for strengthening halal tourism governance, ensuring legal certainty, consumer protection, and sustainable tourism development. Accordingly, enhanced government engagement through legal education, technical assistance, and consistent supervision is essential to improve licensing compliance in emerging halal tourism destinations.